PENGARUH SELF-REGULATED LEARNING DAN PSYCHOLOGICAL WELL-BEING DALAM MENGHADAPI STRES AKADEMIK MAHASISWA TINGKAT AKHIR - Zuhroni, Harkit; Alifa Asyafila Rahmadani (IMTIYAZ: Jurnal Ilmu Keislaman, 2026)
Academic stress is a common psychological issue experienced by final-year university students, particularly in facing thesis completion and graduation requirements. This study aimed to examine the influence of self-regulated learning (SRL) and psychological well-being (PWB) on academic stress among final-year students. The research employed a quantitative approach with an Cross-Sectional design. The participants were final-year students who were in the process of completing their undergraduate thesis. A total of 90 students were selected using a saturated sampling technique. Data were collected through validated and reliable self-report questionnaires measuring academic stress, self-regulated learning, and psychological well-being. The data were analyzed using multiple linear regression with the assistance of SPSS. The results indicated that partially, self-regulated learning did not have a significant effect on academic stress (p > .05) with a contribution of 0.8% (R² = .008) and a negative direction. Similarly, psychological well-being did not show a significant effect on academic stress (p > .05) with a contribution of 0.2% (R² = .002) and a negative direction. Simultaneously, self-regulated learning and psychological well-being did not significantly predict academic stress, with a coefficient of determination of 1.3% (R² = .013), indicating that 98.7% of the variance in academic stress was influenced by other factors outside the research model.